2016
DOI: 10.1016/j.scriptamat.2015.12.028
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for metal–diamond composite coating deposition with cold spray and formation mechanism

Abstract: Rocco (2016) A novel method for metal-diamond composite coating deposition with cold spray and formation mechanism. Scripta Materialia, 115 . pp. 10-13. ISSN 1359-6462 Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/38904/1/Diamond%20Paper-Revised%20v3-accepted %20version.pdf The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…In our previous work, even higher value of 56 wt.% was obtained by the EDS 188 measurements. However, it is rather safe not to attribute the difference to a change in deposition efficiency 189 as the higher value was obtained from coating fracture (i.e., not polished) surfaces [34]. In the previous cold …”
Section: Numerical Methodology 135mentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous work, even higher value of 56 wt.% was obtained by the EDS 188 measurements. However, it is rather safe not to attribute the difference to a change in deposition efficiency 189 as the higher value was obtained from coating fracture (i.e., not polished) surfaces [34]. In the previous cold …”
Section: Numerical Methodology 135mentioning
confidence: 99%
“…Diamond-reinforced metal matrix composites (DMMC) are novel materials in which the metallic phase 33 acts as a binder (yielding the DMMC deformable and machinable), while the reinforcement diamond phase 34 helps to improve the material properties. Currently, the common ways to fabricate bulk DMMC are powder techniques for producing bulk DMMC, these thermal spray techniques also require high working 42 temperatures and the films/coatings therefore potentially face identical problems (in particular, 43 graphitization of the diamond content [17]).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Such investigation is of great importance for a better understanding of the bonding mechanism between coating and substrate. For example, Aldwell et al [25] observed the fracture morphology and impact morphology of deposited particle by using cavitation test, which gave some important insight into bonding features. Chen et al [24] successfully observed the dimple-like fractures on contact surface of deposited particle which is detached from substrate by a tensile test machine.…”
Section: Introductionmentioning
confidence: 99%